Congres in Dordrecht ter gelegenheid van het 25-jarig bestaan van de afdeling aldaar. Midden, tweede rij: Hoving
Congres in Dordrecht ter gelegenheid van het 25-jarig bestaan van de afdeling aldaar. Midden, tweede rij: Hoving.